ГДЗ по алгебре 7 класс Г.В. Дорофеев упражнение 696

показать содержание

696. Решите уравнение: а) 1/3(x+1) – 2/3(х - 1) = 2/3(х - 3); б) 1/2(Зх + 7) – 3/4 (2х - 2) = 3/4(x + 1); в) х(х - 3) + х(2х - 1) = Зх(х - 2) - 3; г) 3 + 2х(3х - 4) = 4х(2х + 5) - 2х(х - 1); д) х(х + 1)(х - 10) = (х - 1)(х - 3)(х - 5); е) (х - 1)(х - 4)(х + 7) = х(х + 1)^2.

учебник / упражнение / 696
696. Решите уравнение:
а) 1/3(x+1) – 2/3(х - 1) = 2/3(х - 3);
б) 1/2(Зх + 7) – 3/4 (2х - 2) = 3/4(x + 1);
в) х(х - 3) + х(2х - 1) = Зх(х - 2) - 3;
г) 3 + 2х(3х - 4) = 4х(2х + 5) - 2х(х - 1);
д) х(х + 1)(х - 10) = (х - 1)(х - 3)(х - 5);
е) (х - 1)(х - 4)(х + 7) = х(х + 1)^2.
решебник / упражнение / 696
696. Решите уравнение:
а) 1/3(x+1) – 2/3(х - 1) = 2/3(х - 3);
б) 1/2(Зх + 7) – 3/4 (2х - 2) = 3/4(x + 1);
в) х(х - 3) + х(2х - 1) = Зх(х - 2) - 3;
г) 3 + 2х(3х - 4) = 4х(2х + 5) - 2х(х - 1);
д) х(х + 1)(х - 10) = (х - 1)(х - 3)(х - 5);
е) (х - 1)(х - 4)(х + 7) = х(х + 1)^2. 696. Решите уравнение:
а) 1/3(x+1) – 2/3(х - 1) = 2/3(х - 3);
б) 1/2(Зх + 7) – 3/4 (2х - 2) = 3/4(x + 1);
в) х(х - 3) + х(2х - 1) = Зх(х - 2) - 3;
г) 3 + 2х(3х - 4) = 4х(2х + 5) - 2х(х - 1);
д) х(х + 1)(х - 10) = (х - 1)(х - 3)(х - 5);
е) (х - 1)(х - 4)(х + 7) = х(х + 1)^2. 696. Решите уравнение:
а) 1/3(x+1) – 2/3(х - 1) = 2/3(х - 3);
б) 1/2(Зх + 7) – 3/4 (2х - 2) = 3/4(x + 1);
в) х(х - 3) + х(2х - 1) = Зх(х - 2) - 3;
г) 3 + 2х(3х - 4) = 4х(2х + 5) - 2х(х - 1);
д) х(х + 1)(х - 10) = (х - 1)(х - 3)(х - 5);
е) (х - 1)(х - 4)(х + 7) = х(х + 1)^2.